Teleostean fishes may have developed an efficient Na+ uptake for adaptation to the freshwater system - Tseng, Yung-Che; Yan, Jia-Jiun; Furukawa, Fumiya; Chen, Ruo-Dong; Lee, Jay-Ron; Tsou, Yi-Ling; Liu, Tzu-Yen; Tang, Yu-Hsin; Hwang, Pung-Pung (Frontiers in Physiology, 2022)
Understanding Na+ uptake mechanisms in vertebrates has been a research priority since vertebrate ancestors were thought to originate from hyperosmotic marine habitats to the hypoosmotic freshwater system. Given the evolutionary success of osmoregulator teleosts, these freshwater conquerors from the marine habitats are reasonably considered to develop the traits of absorbing Na+ from the Na+-poor circumstances for ionic homeostasis. However, in teleosts, the loss of epithelial Na+ channel (ENaC) has long been a mystery and an issue under debate in the evolution of vertebrates. In this study, we evaluate the idea that energetic efficiency in teleosts may have been improved by selection for ENaC loss and an evolved energy-saving alternative, the Na+/H+ exchangers (NHE3)-mediated Na+ uptake/NH4+ excretion machinery. The present study approaches this question from the lamprey, a pioneer invader of freshwater habitats, initially developed ENaC-mediated Na+ uptake driven by energy-consuming apical H+-ATPase (VHA) in the gills, similar to amphibian skin and external gills. Later, teleosts may have intensified ammonotelism to generate larger NH4+ outward gradients that facilitate NHE3-mediated Na+ uptake against an unfavorable Na+ gradient in freshwater without consuming additional ATP. Therefore, this study provides a fresh starting point for expanding our understanding of vertebrate ion regulation and environmental adaptation within the framework of the energy constraint concept.